Theoretical aspects of defining the concept of "students‟self-identification - Berdo, R (Problems of Engineer-Pedagogical Education, 2019)
The aim of the article is to clarify, specify and theoretically define the essential characteristics and means of students' self-identification and its functions in the context of higher education reforms in Ukraine. The term “self-identification” is gradually becoming widely used both in everyday life and in the sphere of scientific research. In relation to the aforementioned topic, the most frequent research niche is sociological and psychological positions of students‟ self-identification as one of the types of self-processes of an individual. However, due to the European vector of higher education in Ukraine there is a need to develop future specialists‟ spiritual and cultural values in addition to expanding their know ledge. As for the pedagogical aspects, there is no clear definition of this issue in scientific literature. The phenomenon of an individual‟s self-identification was first examined during postmodernism. The issue of boosting students‟ self-identification becomes topical due to humanization of education, in crease in the accreditation level and expansion of the autonomy of secondary educational institution. The “identity” concept is viewed as a conceptual construct of the self-identification process. The author has discovered that the consequence of the identity development during adolescence is the formation of the individual‟s self-consciousness, whose product is the “Self-concept”. Furthermore, the selfness (the personality uniqueness) is investigated as a “Self-concept” component. This leads to the conclusion that the selfness is an element of the individual‟s personal development and the process of the “Self” formation. The author analyzed approaches to defining the “self-identification” concept, which, as a result, made it possible to group the scientists‟ opinions according to the directions and to distinguish the intrinsic characteristics of each approach. It allows defining the uncertainty of the self-identification concept. Consequently, the self-identification functions are defined as part of the pedagogical process. In addition, the students‟ self-identification concept is defined in a new signification. The implemented studies allow concluding that there is a need to investigate the development of students‟ self-identification with the help of other participants of the psychological and pedagogical process.